1996
DOI: 10.1055/s-2008-1066508
|View full text |Cite
|
Sign up to set email alerts
|

Motor Function of the Esophagus After Caustic Burn

Abstract: During the subacute and chronic phases of esophagitis due to ingestion of a caustic substance, the patient commonly displays stricture, esophageal rigidity and dysphagia. We used esophageal manometry, radiology, pH monitoring and 99mTc scintigraphy to investigate esophageal motor function in 25 children (mean age 24 +/- 7 months) with chronic esophagitis after second- and/or third-degree caustic burns. The results were compared with those for a control group of 12 children (mean age 32 +/- 19 months) under sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 3 publications
0
14
0
1
Order By: Relevance
“…Bautista et al (8) have found a higher prevalence of oesophagitis in patients with CES. In our study, one third (14 of 52) of patients with CES had oesophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…Bautista et al (8) have found a higher prevalence of oesophagitis in patients with CES. In our study, one third (14 of 52) of patients with CES had oesophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, esophageal injuries are equally deep and result in strictures in about 30% of all accidents (8)(9)(10). Recent studies have reported motor dysfunction after second-or third-degree burns and complete absence of peristalsis, and low-amplitude waves after swallows were found in 70% of recordings on manometry (5,11). Low-amplitude aperistaltic contractions and narrowing and shortening of the esophagus have been considered to account for impaired esophageal motor function (5,6,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported motor dysfunction after second-or third-degree burns and complete absence of peristalsis, and low-amplitude waves after swallows were found in 70% of recordings on manometry (5,11). Low-amplitude aperistaltic contractions and narrowing and shortening of the esophagus have been considered to account for impaired esophageal motor function (5,6,(11)(12)(13). These studies indicated that development of esophageal stricture, impaired motility, and gastroesophageal reflux are very frequent outcomes of caustic esophageal burns and should be considered when evaluating symptoms and defining therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations